Disturbance rejection control of yaw channel of a small-scale unmanned helicopter via Takagi–Sugeno disturbance modeling approach. (20th October 2016) - Fan, Xiangxiang; Yi, Yang; Zhang, Tianping
In this article, the disturbance estimation and rejection problem are discussed for the yaw channel dynamics of small-scale unmanned helicopter subject to mismatched disturbances. Following Takagi–Sugeno fuzzy description for unknown nonlinear disturbances, a composite control input is designed to attenuate the influence of mismatched disturbances in system output channel by combining state feedback control law, disturbance observer, and well-designed disturbance compensator. The satisfactory control performances can be verified using linear inequality optimization algorithm. Simulation results on a yaw channel dynamical system can reflect the feasibility and effectiveness of the proposed disturbance rejection approach.